Killing England : the brutal struggle for American independence - O'Reilly, Bill; Dugard, Martin (New York, New York : Henry Holt and Company, 2017)
"In a book told through the eyes of George Washington, Benjamin Franklin, Thomas Jefferson and Great Britain$1 (Bs King George III, the authors chronicle the path to independence in gripping detail, taking the reader from the battlefields of America to the royal courts of Europe" --s
Includes index.
Keywords: United States -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783.